2013
DOI: 10.1371/journal.pone.0071767
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Competitive Ability between Plants from Nonnative and Native Populations of a Tropical Invader Relates to Adaptive Responses in Abiotic and Biotic Environments

Abstract: The evolution of competitive ability of invasive plant species is generally studied in the context of adaptive responses to novel biotic environments (enemy release) in introduced ranges. However, invasive plants may also respond to novel abiotic environments. Here we studied differences in competitive ability between Chromolaena odorata plants of populations from nonnative versus native ranges, considering biogeographical differences in both biotic and abiotic environments. An intraspecific competition experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
2
25
2
Order By: Relevance
“…, Liao et al. ). Increased growth rates at range edges have also been found due to natural range expansion and poleward migration of species (Evans et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Liao et al. ). Increased growth rates at range edges have also been found due to natural range expansion and poleward migration of species (Evans et al.…”
Section: Discussionmentioning
confidence: 99%
“…With ranges shifting due to natural and anthropogenic causes, there are multiple ways selection can occur. Many studies have shown the evolution of increased growth rate of invaders in invaded habitats (Matlaga et al 2012, Liao et al 2013). Increased growth rates at range edges have also been found due to natural range expansion and poleward migration of species (Evans et al 2013, Schwarzer et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of assuming PLA had no effect in these studies, its effect was treated as ‘not applicable’ in our dataset, which will not influence the overall effect of PLA for all cases. Likewise, seven studies considered the responses to environmental gradients without distinguishing the differences among genotypes from the introduced range, so the effects of LOC were also treated as “not applicable” (Sultan , Bossdorf et al , Wang et al , Flory et al , Lamarque et al , Liao et al , Travlos ). As to the other twelve studies that compared the genotypic differences among multiple genotypes under one environmental condition, the effects of PLA were also treated as ‘not applicable’.…”
Section: Methodsmentioning
confidence: 99%
“…A few EICA studies have performed studies of intraspecific competition (Felker‐Quinn, Schweitzer, & Bailey, ; Feng et al, , ; Parker et al, ; Qin et al, ), which is important because intraspecific competition eliminates the potential confounding effects of using a heterospecific as a “phytometer.” Pots contained a mixture of 60% forest topsoil and 40% river sand. Topsoil was used as a natural supply of macro‐ and micronutrients, while river sand provided adequate drainage and facilitated the harvesting of fine roots (Liao, Zhang, Barclay, & Feng, ). All seedlings were initially grown in shade with 50% irradiance for 4 weeks to facilitate initial survival; after this period, they were grown in full sun.…”
Section: Methodsmentioning
confidence: 99%